(3MGTjI Ydi GdTQM GdYVOi deNJUQ GHf GdMGLHs - (3GdBeOi (B/ (3Ydj Hf CHi HcQs; (3YHO GdQMef Hf CMeO Hf YHO GdZaGQ, CHh GdaVd, nYoVO GdOjf GdEjLj,J (B756 (3g` s
(3ChdgG (B:s
(3GbJaGA deG hQO ai GdCNHGQ hGbJOGA HWQjbI GdCNjGQ s
(3BNQgG (B:s
(3hEPG JUhQJ gPG GdcdGe YQaJ Gfg jecf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ ai fgGjI GdeNWhW HNW eNJda bdjd GdfbW s
(3hQO GdYfhGf GdCUdi ai cX (B1853/2s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3CUhd Gdabgs